Metabolic accompaniment of quantitative-qualitative blood pressure clusters in patients of Truskavets' spa - Nataliya Kozyavkina; Yuliya Vovchyna; Nataliya Voronych-Semchenko; Walery Zukow; Igor Popovych (Kazimierz Wielki University, 2022)
Background. Earlier we studied the neural and endocrine accompaniments of quantitative-qualitative blood pressure (BP) clusters of profile patients of Truskavets' spa. The purpose of this study is to clarify the metabolic accompaniment in the same contingent. Materials and methods. Under an observations were 44 patients with chronic pyelonephritis and cholecystitis in the phase of remission. Testing was performed twice - on admission and after 7-10 days of standard balneotherapy. The main object of the study was BP (tonometer "Omron M4-I", Netherlands). The plasma levels of lipids, glucose, nitrogenous metabolites and electrolytes as well as urinary excretion of last two were determined. In addition, electrokinetics and cholecystokinetics indexes were determined. Results. The forward stepwise program identified 21 parameters as characteristic of quantitative-qualitative blood pressure clusters. In addition to BP parameters by default, the most informative among them are sodium and uric acid daily excretion as well as plasma phosphate and magnesium, whose levels are maximal in patients with hypertension, while minimal in patients with low norm BP, on the one hand, and electrokinetics index, the level of which are polar, on the other hand. The accuracy of patient classification is 97,7%. Conclusion. The quantitative-qualitative blood pressure clusters have a characteristic metabolic accompaniment.